Severe Dilatation of Coronary Artery Ostium Complicating Sinus of Valsalva Aneurysm: Differential Diagnosis and Review of the Literature - Paul Bamford; Nicholas Collins (Case Reports in Cardiology)
Coronary artery dilatation may be due to various aetiologies including congenital anomalies, atherosclerotic coronary disease, and Kawasakis disease. We describe a case characterised by apparent severe dilatation of the right coronary artery ostium in an asymptomatic male. Subsequent imaging and surgical intervention documented the presence of a sinus of Valsalva aneurysm extending into the ostium of the right coronary artery. This represents an unusual manifestation of a sinus of Valsalva aneurysm. The underlying pathophysiology, differential diagnosis, role of surgical management, and outcomes are discussed.